Surgical fixation by mesh plate and intraoperative safe techniques for the manubrium sterni. (June 2021) - Takeda, Shinsuke; Yamamoto, Michiro; Mitsuya, So; Hashimoto, Kumiko; Hirata, Hitoshi; Yamauchi, Ken-ichi
Abstract: Plate osteosynthesis for oblique fracture of the manubrium sterni is quite rare. We present a case of a 37-year-old man with oblique fracture of the manubrium sterni caused by a traumatic injury. He was operated on using a variable-angle locking compression plate Mesh Plate 2.4/2.7 and had a good postoperative result. We also discuss intraoperative safe techniques such as use of a cement spatula for reduction support tools and depth-limited drilling to prevent excess drilling of the opposite cortex.